The Effect of Service Quality and Price on Consumer Satisfaction in the Seblak Tampir Ciparay Business in Bandung Regency - Adji, Hangayomi; Oktaviani, Erni (Journal of Economic Empowerment Strategy (JEES), 2026)
This study aims to analyze the influence of service quality and price on consumer satisfaction in the Seblak Tampir Ciparay business, Bandung Regency. Consumer satisfaction is a crucial factor in determining business success and sustainability, especially in the culinary sector, which faces a high level of competition. Service quality and competitive pricing are important elements that can attract new customers while maintaining existing ones. In this context, service quality includes service speed, staff friendliness, cleanliness of the place, and the ability to fulfill consumer needs and expectations. Meanwhile, price reflects consumers’ perceptions of the value received compared to the costs incurred. This research uses a quantitative approach with descriptive and verification methods. Data were collected through questionnaires distributed to active consumers of Seblak Tampir Ciparay, who were considered representative of the customer population. Data analysis was conducted using multiple linear regression, t-tests, F-tests, and the coefficient of determination (R²) with the assistance of SPSS version 22. This approach allows researchers not only to describe actual conditions but also to test the influence of service quality and price on consumer satisfaction both partially and simultaneously. The results show that service quality and price have a significant influence on consumer satisfaction, both partially and simultaneously. Good service quality increases consumer satisfaction because customers feel valued and receive a satisfying experience. Prices that are appropriate to consumers’ perceived value of the products also affect customers’ decisions to make repeat purchases. Simultaneously, these two variables contribute 50.69% to consumer satisfaction, while the remaining percentage is influenced by other factors such as location, promotion, or product taste.